Destruction of emerging organic contaminants and bacteria in water by TiO2- based photocatalysts under visible-light led irradiation - Wang, Xiaoping. (2013)
TiO2-assisted heterogeneous photocatalysis has been proved to be a very promising technique for water treatment and purification such as degradation of recalcitrant organic contaminants and disinfection. However, the widespread and practical applications of TiO2 photocatalysis are rather limited, since the wide band gap of TiO2 restricts its photoexcitation to the UV region. In order to effectively utilize visible light or indoor light to initiate photocatalysis, this study aims to fabricate various types of visible-light active TiO2-based photocatalysts for destruction of aqueous emerging organic contaminants and/or pathogens.